Aggregation-induced phosphorescence enhancement of Mn-doped ZnS quantum dots: the role of dot-to-dot distance. Issue 19 (4th May 2018) - Zhang, Jinyi; Tang, Dandan; Yao, Yadong; Hou, Xiandeng; Wu, Peng
Abstract : The aggregation-induced phosphorescence enhancement (AIPE) of Mn-doped ZnS QDs is highly dependent on the dot-to-dot distance in the aggregates. Abstract : Assembled nanoparticles promote many applications in optics due to their instinct properties. The aggregation-induced phosphorescence enhancement (AIPE) of Mn-doped ZnS quantum dots (QDs) is widely used in biosensing, but the mechanism of such an enhancement is still unproven. This study explores the mechanism of the interesting finding of AIPE of Mn-doped ZnS QDs. To induce the aggregation of QDs, the method of electrostatic assembly was explored herein: negatively charged QDs were aggregated with protamine and positively charged QDs were aggregated with heparin. Using several ligands with hierarchical molecular weights for capping Mn-doped ZnS QDs, it was found that the AIPE of Mn-doped ZnS QDs was exponentially dependent on the dot-to-dot distance in aggregates. Together with detailed analysis of both the steady- and transient-state luminescence behaviors of Mn-doped ZnS QDs before and after aggregation, charge transfer from one dot (surface traps) to another (dopant bands) was identified as the driving factor for AIPE. Moreover, the d-band of the Mn 2+ dopants was essential for the AIPE since it acts as the acceptor for the transferred charge from neighboring QDs. These conclusions can significantly contribute for better understanding of this interesting luminescence mechanism and future designing of the most suitable sensing systems.